2023
DOI: 10.3390/agriculture13010214
|View full text |Cite
|
Sign up to set email alerts
|

Time, Spatial and Component Characteristics of Agricultural Carbon Emissions of China

Abstract: In this study, the time trend, regional distribution and component characteristics of the agricultural carbon emissions (ACEs) of China are analyzed. The estimation methods of each component of the ACE are introduced. According to the annually provincial panel data set with the 31 provinces from 1996 to 2019, the time trend, regional distribution and component characteristics are empirically discussed. Meanwhile, since it is also worthwhile to explore the effect of the ACE on economic growth, econometric model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It is worth noting that narrow-sense agriculture mainly refers to planting industry, and its carbon emission sources are generally defined as effective irrigation area, the total sown area of crops, the net amount of agricultural chemical fertilizer, the amount of agricultural diesel, pesticide and agricultural plastic film [ 31 ]. While broad-sense agriculture in our study includes agriculture, forestry, animal husbandry and fishery (note: the agriculture mentioned in the following context is the broad-sense agriculture studied in this paper unless otherwise specified), whose carbon emission measurement index system has not been unified at present, with coefficient misuse, carbon sources duplication, unclear sources and other circumstances [ 5 , 32 , 33 ]. According to our research theme and perspective, this paper improves and tries to perfect the agricultural carbon emission measurement indicator system under a clarification that carbon emissions are not only CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that narrow-sense agriculture mainly refers to planting industry, and its carbon emission sources are generally defined as effective irrigation area, the total sown area of crops, the net amount of agricultural chemical fertilizer, the amount of agricultural diesel, pesticide and agricultural plastic film [ 31 ]. While broad-sense agriculture in our study includes agriculture, forestry, animal husbandry and fishery (note: the agriculture mentioned in the following context is the broad-sense agriculture studied in this paper unless otherwise specified), whose carbon emission measurement index system has not been unified at present, with coefficient misuse, carbon sources duplication, unclear sources and other circumstances [ 5 , 32 , 33 ]. According to our research theme and perspective, this paper improves and tries to perfect the agricultural carbon emission measurement indicator system under a clarification that carbon emissions are not only CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Carbon emissions are often measured from different components, industrial activities and regions, and so are agricultural carbon emissions. Li and Wang (2023) introduced an estimation method of various components about agricultural carbon emissions, and found that China's agricultural carbon emissions presented an inverted “U-shape” from 1995 to 2020 and mainly came from carbon emissions generated by fertilizer utilization [ 5 ]. With the deepening of economic globalization, agricultural trade has become an important part of the country's social and economic development.…”
Section: Introductionmentioning
confidence: 99%
“…The system includes two links: livestock and poultry breeding energy consumption and slaughtering and processing. In the process of raising livestock and poultry, a large amount of electricity, coal and other energy will be consumed, which will directly or indirectly cause carbon emissions [24]. The amount of CO2 produced by livestock and poultry feeding can be calculated according to the following formula:…”
Section: Calculation Of Animal Husbandry Carbon Emissionsmentioning
confidence: 99%
“…The impact of large-scale farmland management on carbon emissions is re ected in the different choices of farmers in the use of chemical fertilizers and farmland irrigation, resulting in differences in agricultural carbon emissions, among which the production and use of chemical fertilizers, pesticides, and other chemicals had the greatest impact, Zhang Xiaojie [23] et al reached similar conclusions using empirical research. China's agricultural production is highly dependent on chemical inputs [12], so the average farmer may choose to change the scale of farmland operations and the input of chemicals such as fertilizers in order to increase agricultural production. Large-scale farmers are often willing to accept new technologies for e cient use of chemical fertilizers[18], while farmers with small-scale operations tend to have less technical mastery of the scienti c application of fertilizers and other chemicals [15], so the scale of farmland management can indirectly affect carbon emissions through the input of fertilizers and other chemicals.…”
Section: Impact Of Farmland Management Scale Agricultural Carbon Emis...mentioning
confidence: 99%